Sinteză narativă: asocierea dintre rezistența la antimicrobiene cu implicații ale micro-organismelor Gram-negative și schimbările climatice (One Health & Risk Management, 2023)
NARRATIVE SYNTHESIS: ASSOCIATION BETWEEN ANTIMICROBIAL RESISTANCE WITH IMPLICATIONS OF GRAM-NEGATIVE MICROORGANISMS AND CLIMATE CHANGEIntroduction. Both antimicrobial resistance and climate change are critical issues for the medical system, and they mutually exacerbate each other.Material and methods. A narrative synthesis study was undertaken, covering the research period from 2008 to 2023. The terms used for literature selection focused on three aspects: infectious diseases, particularly those caused by gram-negative microorganisms, the phenomenon of resistance to antimicrobial preparations, and climatic variables. The initial search yielded 5058 articles, and after selecting those available in open access with full text, 2863 articles were considered. Following the exclusion of records unrelated to the study and a review of abstracts, 31 eligible papers remained.Results. Antimicrobial resistance and climate change share a concerning interrelationship: global warming generates new habitats for resistant bacteria, including gram-negative strains, escalating the challenges faced by global human, animal, and environmental health systems. Research affirms that elevated temperatures, coupled with factors like flooding and high population density, contribute to heightened resistance to antimicrobial treatments. Mapping indicates a correlation between rising temperatures and regions where higher levels of resistant bacteria are prevalent.Conclusions. The literature review underscored the scarcity of research on the direct correlation between antimicrobial resistance and climate change, emphasizing the need for further investigation in this domain.